Energy targeting for an office building : a case study of Thai Airways buildings - Jirawat Nooritanon; Surapong Chiraratananon; Exell, R.H.B.; Supachart C.; Commission of the European Communities (Bangkok : Asian Institute of Technology, 1993)
The commercial high-rise building in Bangkok have been constructed at rapid growth and their energy consumption are varied in the wide range due to the diversity in design construction, using purpose, operating period and etc. To consider the way for finding suitable amount of energy consumption of each building, energy targeting is needed. In this study, the energy targeting based on OTTV concept, proposed by S. Chirarattananon, is modify by considering the effects of (i) different type of areas, (ii) the use of OTTV calculation out-of normal office hours. To see the effects from (ii), one computer program specially used to calculated TDeq for any specific operating periods and types of wall materials is written. And the one existing building complex which is Thai Airways Building Complex is selected as a case study. This complex comprises with five buildings; Building No. I: the Office Building; Building No.2: Canteen; Building No.4: Mechanical building; Building No.6: Simulation Building and Building No.9: Crew building. The first three buildings are operated during normal office hours while the remaining buildings are operated from 7.00 to 24.00. After the analysis of past four years annual energy data and doing energy audit from the complex completed, the table for setting energy target is created and data from energy audit and recommended stand are filled. The final results show that by taking in account of different type of areas the accuracy of energy target can be improved around 40 percent but for using OTTV accounted for actual operating period, accuracy can be improved only 4 percent. Then summary can be written that within 95 percent of accuracy needs the ordinary OTTV method and standard value from table can be used for setting energy target. The final part is sensitivity analysis. The results show about the influences of change in each variable which will affect to the change in total energy consumption for each type of area in the complex. And the analysis can prove that errors from measurement have very small effect to the improvement on actual total energy consumption by changing the related parameters.
Thesis (M.Eng.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering.
Keywords: Building -- Thailand -- Bangkok -- Energy conservation